2011
DOI: 10.1093/carcin/bgr297
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of the mechanism of benzene-induced leukemia in humans: implications for risk assessment

Abstract: Benzene causes acute myeloid leukemia and probably other hematological malignancies. As benzene also causes hematotoxicity even in workers exposed to levels below the US permissible occupational exposure limit of 1 part per million, further assessment of the health risks associated with its exposure, particularly at low levels, is needed. Here, we describe the probable mechanism by which benzene induces leukemia involving the targeting of critical genes and pathways through the induction of genetic, chromosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
202
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(210 citation statements)
references
References 204 publications
(207 reference statements)
3
202
0
5
Order By: Relevance
“…It is speculated that genetic and lifestyle factors influence the toxic effects of benzene, but current evidence is inconclusive. 29,30 Scientists postulate that the resultants of benzene metabolites are responsible for benzene toxicity because these metabolites can alkylate proteins and DNA. 31 Previous studies have shown that individuals vary in their susceptibility to the adverse effects of benzene, probably due to differences in metabolic genes and corresponding enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that genetic and lifestyle factors influence the toxic effects of benzene, but current evidence is inconclusive. 29,30 Scientists postulate that the resultants of benzene metabolites are responsible for benzene toxicity because these metabolites can alkylate proteins and DNA. 31 Previous studies have shown that individuals vary in their susceptibility to the adverse effects of benzene, probably due to differences in metabolic genes and corresponding enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The main targets of toxic effect are the respiratory and the nervous system. Ethylene oxide, formaldehyde and benzene can damage DNA and induce cancer as recognised by the International Agency for Research on Cancer, while some fumigants, such as methyl bromide, are suspected carcinogens [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to AML and MDS, studies point to a correlation of exposition to benzene with a broad spectrum of malignant diseases of the hematopoietic and lymphatic systems: Non-Hodgkin's Lymphoma, chronic or acute lymphoid leukemia, and multiple myeloma. It should be further emphasized that organic solvents -the chemical group of which benzene is a part and that is almost always present in the form of a mixture of products -are demonstrably associated with various other types of cancer such as breast and brain cancer [6][7][8] . Benzene and other chemical contaminants become increasingly important in light of the rapid and intense changes in recent decades, with a huge impact on the workplace, the environment, and on health.…”
Section: Introductionmentioning
confidence: 99%